Sacred scripture and secular struggles - Meconi, David Vincent. (The Bible in Ancient Christianity, 2015)
Twelve leading scholars have collaborated on this unique volume, bringing their biblical and patristic expertise together to show how the first followers of Jesus used their own canonical scriptures to address concerns central to life in the Roman Empire. Sacred Scripture and Secular Struggles offers an overview of how early Christians approached and appropriated biblical texts in addressing wider societal issues of imperial power, slavery, the use of wealth, suicide and other fundamental issues brought about by the convergence of empire and ecclesia.